A Bamboo-Inspired Exoskeleton (BiEXO) Based on Carbon Fiber for Shoulder and Elbow Joints - Zahedi, Ahmad; Wang, Yansong; Lau, Nathan; Ang, Wei Tech; Zhang, Dingguo (IEEE transactions on medical robotics and bionics, 2023)
This paper presents a novel cable-driven exoskeleton (BiEXO) for the upper limb including shoulder and elbow joints. BiEXO is made of carbon fiber that is inspired by the Bamboo structure. The key components of BiEXO are carbon fiber tubes that mimic bamboo tubes. A combined driver is developed for BiEXO with two cable-driven mechanisms (CDMs) and a power transmission belt (PTB). The CDMs are used for shoulder and elbow flexion/extension movement utilizing cables to mimic the skeletal muscle's function, while the PTB system drives a shoulder link to mimic the scapula joint for shoulder abduction/adduction movement. Simulation studies and evaluation experiments were performed to demonstrate the efficacy of the overall system. To determine the strength-to-weight of the bamboo-inspired links and guarantee high buckling strength in the face of loads imposed from the user side to the structure, finite element analysis (FEA) was performed. The results show that the carbon fiber link inspired by bamboo has more strength in comparison to the common long carbon fiber tube. The kinematic configuration was modeled by the modified Denavit-Hartenberg (D-H) notation. The mean absolute error (MAE) was 5.9 mm, and the root-mean-square error (RMSE) was 6 mm. In addition, verification experiments by tracking the trajectory in Cartesian space and the wear trials on a subject were carried out on the BiEXO prototype. The satisfactory results indicate BiEXO to be a promising system for rehabilitation or assistance in the future.